General laws of biodiversity: Climatic niches predict plant range size and ecological dominance globally - Gabriel M. Moulatlet; Cory Merow; Brian Maitner; Brad Boyle; Xiao Feng; Amy E. Frazier; Cesar Hinojo-Hinojo; Erica A. Newman; Patrick R. Roehrdanz; Lei Song; Fabricio Villalobos; Pablo A. Marquet; et al. (Proceedings of the National Academy of Sciences, 2025)
A longstanding question in ecology asks whether or not species that achieve large geographic ranges also have large climatic niche breadths. Using a dataset of ~250,000 terrestrial plant species spanning diverse clades (bryophytes, ferns, gymnosperms, and flowering plants), we demonstrate a consistent positive relationship between geographic range size and climatic niche breadth across latitudinal and elevational gradients. This relationship holds across major phylogenetic groups, suggesting a general biogeographical rule for range size variation. Our findings indicate that latitudinal and elevational gradients in range size arise from selective pressures and species sorting based on climatic tolerance. Additionally, we show that species with larger range sizes tend to be ecologically dominant, supporting a long-suspected connection between range size, niche breadth, and local and regional abundance. Our results suggest a spectrum of dominance, where species with extensive geographic ranges and broader climatic tolerances tend to be more abundant. We posit that the relationship between range size, niche breadth, and ecological dominance is an emergent macroecological pattern that can be used for understanding and predicting the impacts of climate change on species distributions.